DEVELOPMENT OF THE CONSTRUCTIVE-TECHNOLOGICAL SCHEME OF THE DEVICE FOR RAW PROCESSING OF RAW MATERIALS BY GRINDING, HOMOGENIZATION AND CAVITATION DESTRUCTION - Aitbayeva, З. К.; Mamataeva, Д.У (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Based on the functional description of the scheme for the primary preparation of cattle waste and fermentation of the substrate in a psychrophilic mode, a device for processing raw materials by grinding, homogonization, and cavitation destruction has been developed. The regularities of grinding and uniformity of the composition of the substrate, the distribution of heat and anaerobic digestion in a psychrophilic mode in a bioreactor are considered. There are various solid particles in livestock waste, such as sand, clay, etc., which causes the formation of sediment, while light materials like straw and others rise to the surface of the bioreactor and form a crust, which leads to a decrease in gas formation. Therefore, it is necessary to grind plant residues – straw, scraps, etc., before loading into the reactor, and strive for the absence of solids in the feed. The calculation of determining the volume of the pipe. The number of cycles required for the primary processing of raw materials of the maximum possible volume of biomass is determined. A structural and technological scheme of a device for processing raw materials by grinding, homogenization and cavitation distraction has been developed.